Berberine inhibits low shear stress-induced vascular endothelial inflammation via decreasing phosphorylation of Akt and IRF3. (December 2022) - Lv, Yifei; Yang, Hongfeng; Ye, Peng; Qian, Zhiyuan; Wang, Dongchen; Kong, Chaohua; Gu, Yue; Zhou, Wenying; Chen, Shaoliang; Zhu, Linlin
Abstract: Background: Low shear stress (LSS) is closely related to vascular endothelial inflammation and the development of atherosclerosis. Berberine (BBR), a natural compound isolated from Coptis chinensis, has been reported to exert anti-inflammatory and antiatherosclerotic effects. However, the role of berberine in low shear stress-induced endothelial inflammation remains unclear. Methods: The role of berberine in low shear stress-induced vascular endothelial inflammation was investigated in human umbilical vein endothelial cells (HUVECs) using a plate flow chamber in vitro and in mice with an established LSS model by partial ligation of the carotid artery in vivo. Results: First, in vitro experiments demonstrated that BBR significantly decreased the expression of vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) and the phosphorylation of Akt in HUVECs induced by low shear stress. Moreover, BBR significantly inhibited the low shear stress-mediated phosphorylation of IRF3 and its translocation to the nucleus. Notably, Akt overexpression markedly reversed the inhibitory effects of BBR on LSS-induced IRF3 activation and ICAM-1 expression. Moreover, in vivo experiments showed that BBR markedly decreased intimal ICAM-1 and IRF3 in the LSS areas of partially ligated carotid arteries in mice; however, EC-specific Akt overexpression mediated by adeno-associated viruses abolished the anti-inflammatory effect of BBR. Conclusion: Taken together, our findings suggest that BBR treatment attenuates LSS-induced vascular endothelial inflammation by decreasing the activation of the Akt/IRF3 signalling pathway. Highlights: Endothelial cell inflammation is the key to atherosclerosis formation. Low shear stress of blood flow is essential for endothelial cell inflammation. Berberine has a protective effect on endothelial function. Berberine reverses low shear stress mediated endothelial inflammation via the Akt-IRF3 signaling pathway.